1=0.5x-0.6x-7

Simple and best practice solution for 1=0.5x-0.6x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1=0.5x-0.6x-7 equation:


Simplifying
1 = 0.5x + -0.6x + -7

Reorder the terms:
1 = -7 + 0.5x + -0.6x

Combine like terms: 0.5x + -0.6x = -0.1x
1 = -7 + -0.1x

Solving
1 = -7 + -0.1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.1x' to each side of the equation.
1 + 0.1x = -7 + -0.1x + 0.1x

Combine like terms: -0.1x + 0.1x = 0.0
1 + 0.1x = -7 + 0.0
1 + 0.1x = -7

Add '-1' to each side of the equation.
1 + -1 + 0.1x = -7 + -1

Combine like terms: 1 + -1 = 0
0 + 0.1x = -7 + -1
0.1x = -7 + -1

Combine like terms: -7 + -1 = -8
0.1x = -8

Divide each side by '0.1'.
x = -80

Simplifying
x = -80

See similar equations:

| 71+25+x=180 | | 93+50+x=180 | | 96+45+x=180 | | 104+29+x=180 | | 105+23+x=180 | | -73+2y+6=2(4y-2)9 | | 3x+2=-2x-2 | | (f+6)squared=144 | | 42=3v+12 | | 3(x^2-2x-8)=0 | | 6x-2y=-30 | | 5+x=2x-3-8 | | 3(x-6)=6(x-3) | | 360=x+(9x-35)+(x-46)+.5x | | 2x-19=(-5)x+9 | | 2u-11=5(u+2) | | x-7=4x+1 | | 8x+18=3x+-7 | | 6x+1=4x-13 | | (x-15)-(2x-13)=1 | | 6x(6x)+5(3x(3x)-x)-3x= | | 4x-3+90=180 | | f(x)=500-75x | | 3x(x-2)=24 | | 3x(x-2)=23 | | (1+0.05)4= | | A=0.5(b+12)5 | | 2x-6+2x-9=180 | | 9+x+7+x=50 | | 2-3(x-5)=20 | | 23x=10x+5 | | 4-y=230 |

Equations solver categories